Ability to successfully image endometrium on transvaginal ultrasound in asymptomatic postmenopausal women. (9th September 2021) - Goldstein, S. R.; Khafaga, A.
ABSTRACT: Objectives: Numerous studies indicate that endometrial thickness of ≤ 4 mm on transvaginal ultrasound (TVS) is a reliable test to exclude endometrial cancer in women with postmenopausal bleeding (PMB), such that biopsy is not needed. However, not all postmenopausal women have anatomy that allows reliable measurement of endometrial thickness. This study was undertaken to evaluate the frequency of, and the reasons for, an inability to adequately visualize the endometrium on TVS. Methods: A total of 472 consecutive asymptomatic postmenopausal women underwent TVS as part of their routine gynecological care. Their charts and TVS images were reviewed, and, if possible, endometrial thickness was recorded. If the endometrium was not adequately visualized, the reason for inadequacy was recorded, as judged by the examiner. Other demographic characteristics recorded included the number of years since menopause, body mass index (BMI) and current use of hormone replacement therapy. Results: Of the 472 women, 292 (61.9%) had an endometrium that was well visualized, in whom endometrial thickness could be measured reliably (mean, 3.0 (range, 1.0–28.0) mm). In the other 180 postmenopausal women (38.1%), a distinct endometrium was not adequately visualized. The reasons for non‐visualization were fibroids ( n = 95, 20.1% of the overall cohort), adenomyosis ( n = 35, 7.4% of the overall cohort) and an axial uterus ( n = 50, 10.6% of the overall cohort). Mean interval from menopause was 14.0 (range, 1–50) years and 14.1 (range, 1–40) years in the visualized and non‐visualized cohorts, respectively ( P = 0.83). Mean BMI was 23.9 (range, 16.3–41.5) kg/m 2 in the visualized cohort and 25.4 (range, 18.0–39.9) kg/m 2 in the non‐visualized cohort ( P = 0.015). Conclusions: TVS has become an accepted first step in the evaluation of PMB. However, in our cohort, 38.1% of women had anatomical reasons for non‐visualization of the endometrium and lack of a reliable endometrial thickness measurement, including fibroids, adenomyosis or an axial uterus. There was no significant difference between groups in the interval from menopause or current use of hormone replacement therapy, but the mean BMI of the non‐visualized group was significantly higher than in the visualized group. Clinicians should be cognizant of these potential limitations of TVS in the initial evaluation of women with PMB. © 2021 International Society of Ultrasound in Obstetrics and Gynecology.